ANALISIS INFLUENCER MARKETING DALAM MENINGKATKAN BRAND AWARENESS GLXSSY BEAUTE - Lenggihunusa, Audy Yudistira; Chan, Arianis; Hakim, Marsha Aulia (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to analyze the implementation of influencer marketing in increasing the brand awareness of Glxssy Beaute. The research employs a descriptive qualitative approach with data collection techniques including semi-structured interviews, non-participant observation, and secondary document analysis. The research informants consist of the CEO and Founder of Glxssy Beaute, a Digital Marketing Strategist from a marketing agency, two Glxssy Beaute consumers, and two prospective consumers from the target market. The findings indicate that influencer marketing implemented by Glxssy Beaute plays an important role in increasing brand awareness through various campaign stages. Glxssy Beaute optimizes storytelling in influencer marketing by giving influencers the freedom to create authentic content. Overall, the strategy implemented is quite effective; however, improvements are still needed in content quality management to enhance Glxssy Beaute's competitiveness. Keywords: Influencer Marketing, Brand Awareness, Local Beauty Industry